The importance of interreligious dialogue in modern Nigeria (Christian-Muslim relation - Ashimi, Tijani Ahmad (2012)
Nowadays and in this twenty first century, Inter-religious dialogue is gaining momentum and importance at both national and international levels. Perhaps, that is due to its role and goal in building bridges among different religious groups to promote respect, tolerance and peaceful living. Based on above fact, inter-religious dialogue is perhaps; more important in Nigeria than anywhere else, on the grounds that, Nigeria is considered as the most populous country in African continent, and it is moreover, a pluralistic and multi religious society, which is mainly dominated by Islam and Christianity. Yet, in modern Nigeria, the relation between Muslims and their counterpart Christians is in continuous jeopardy (if not deteriorating). As such, the country has experienced various religious violence between these two dominant religious groups, (Islam and Christianity) and these religions are even sometimes depicted as monolithic entities that confront each other in pitched battles. As a result of uncountable battles and confrontations, incalculable human loses and material damages are always attributed to religion. As far as peaceful coexistence is concerned, and as far as religious tolerance is also important, there is no doubt that the best forum to promote Muslims-Christians relationship, and the right tool to tackle reoccurrence of religious conflict in the country is interfaith dialogue. Thus, this humble paper will demonstrate the meaning of inter-religious dialogue according to various scholars followed by the causes behind the need for inter-religious dialogue in Nigerian context, then, mechanisms and methods that can be utilized to achieve the goal of this forum in Nigerian pluralistic society.